Differences between Men and Women in Opportunity Evaluation as a Function of Gender Stereotypes and Stereotype Activation. (July 2013) - Gupta, Vishal K.; Turban, Daniel B.; Pareek, Ashish
Opportunity evaluation represents a core aspect of the entrepreneurial process. Prior research suggests that evaluation of new opportunities is influenced by biases rooted in subjective beliefs, values, and assumptions. In the present study, we used stereotype activation theory to propose that respondent gender (men–women), content of stereotype (masculine–feminine), and the manner in which stereotype information is presented (subtle–blatant) interact to influence evaluations of a new business opportunity. We found that both masculine and feminine stereotype activation influenced men and women's evaluation of a business opportunity differently depending upon whether the stereotype was blatantly or subtly activated. Our results indicate that gender stereotype activation can both boost and impede men and women's subsequent actions on entrepreneurial tasks such as opportunity evaluation, depending on the content of the stereotype and the manner in which it is presented. Implications and directions for future research are discussed.